A survey of the Ghanaian tax system - Abdul Malik; Iddrisu Ross; Edward Abrokwah; Harriet Conron; Andara Kamara; Daniel Nuer (Institute for Fiscal Studies (IFS), 2021)
In its 2020 Ghana CARES 'Obaatanpa' programme, the Government of Ghana emphasised the need to improve domestic revenue mobilisation in order to ensure the realisation of its medium-term fiscal policy and development objectives. In the context of ambitious revenue mobilisation goals and a challenging fiscal outlook, the design of the country's tax system is a crucial issue for policymakers. In this report, we provide a comprehensive overview of Ghana's tax system. This is intended as a repository of key information for researchers, policymakers and the public, as well as highlighting aggregate patterns of note as a first step for identifying challenges and areas for reform.
Keywords: 330; Steuersystem; Steuereinnahmen; Steuerreform; Ghana